Pencirian Plasmon-Polariton Permukaan Melalui Gandingan Parutan - Mat Yunus, W. Mahmood (Universiti Putra Malaysia Press, 1996)
Surface plasmon polariton mode may be excited by photons using grating coupling to provide the necessary extra momentum. Reflectivity measurements at 632.8 nm were carried out on three modulated grating gold films. The gold films were deposited by vacuum evaporation on a silica grating at base pressure for 1O-6 torr. By rotating the grating in azimuth angle direction, where the grooves of the grating are no longer perpendicular to the plane of incidence, the symmetry of the system is broken and polarization conversion phenomenon is introduced. This conversion is strongly enhanced when SPP mode is excited. The dependence of this conversion on angle of incidence and azimuthal angle is discussed in detail. When the grooves are at about 45° to the plane of incidence, maximum conversion is observed.